The mutual relationship between shift work and depressive complaints - a prospective cohort study - Karolien Driesen; Nicole WH Jansen; Ludovic GPM van Amelsvoort; IJmert Kant (Nordic Association of Occupational Safety and Health (NOROSH), 2011)
OBJECTIVE: The aim of this study was to examine longitudinally the mutual relationship between shift work and depressive complaints. METHODS: Data from the ongoing Maastricht cohort study (1998-2008) were used. Firstly, the impact of shift work on the development of depressive complaints, defined as depressed mood, was studied. Both prospective and retrospective approaches were used, conducting, respectively, survival and logistic regression analyses, correcting for possible confounding factors. Secondly, the impact of depressed mood on changes in shift work at one-year follow-up was studied. All analyses were stratified for men and women and, where possible, for age (<45 versus ≥45 years). RESULTS: Overall, the impact of shift work on the development of depressed mood over a ten-year period was rather small, although, male shift workers ≥45 years did contribute to a higher risk of developing depressed mood [hazard risk (HR) 1.37, 95% confidence interval (95% CI) 1.01-1.86]. Retrospective analyses found higher odds of depressed mood and depressive disorder among former or current male shift workers than "never shift workers" [odds ratio (OR) 1.39, 95% CI 1.09-1.79 and OR 1.79, 95% CI 1.32-2.42, respectively]. Results lacked significance when correcting for demographic and work-related factors. Analyses studying the impact of depressed mood on changes in work schedules showed that the risk to change from shift to day work or from shift work to sick leave was higher when depressed mood was reported at baseline [relative risk (RR) shift to day work 1.98, 95% CI 1.13-3.47; RR shift work to sick leave 2.96, 95% CI 2.00-4.29]. CONCLUSIONS: Although shift work did not have a large impact on the development of depressed mood, results might be underestimated due to selection processes and possibly overcorrection.